The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1521/suli.2005.35.6.640
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions Concerning College Student Suicide: Data from Four Universities

Abstract: The issue of suicide, including prevention, intervention, and postvention, continues to be a problem on college campuses. For this study, data concerning a variety of issues related to college student suicide were collected from 1,865 students at four different universities. Incidence, risk factors, and potential solutions are described, as well as implications for mental health professionals in university settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(69 citation statements)
references
References 14 publications
(21 reference statements)
4
63
1
1
Order By: Relevance
“…Less than one third of our respondents felt confident in their ability to convince someone to seek help and perceived themselves as having more than average to a great deal of confidence in their ability to ask someone about suicide and intervene when someone is at risk. These findings are also similar to those found in previous research (Drum, Brownson, Denmark, & Smith, 2009;King et al, 2008;Westefeld et al, 2005).…”
Section: Discussionsupporting
confidence: 93%
“…Less than one third of our respondents felt confident in their ability to convince someone to seek help and perceived themselves as having more than average to a great deal of confidence in their ability to ask someone about suicide and intervene when someone is at risk. These findings are also similar to those found in previous research (Drum, Brownson, Denmark, & Smith, 2009;King et al, 2008;Westefeld et al, 2005).…”
Section: Discussionsupporting
confidence: 93%
“…In studies conducted in other countries, the prevalence of thoughts of suicide were found to be 24%, suicide attempts varied between 5 and 18% (11,(46)(47)(48)(49). Regardless of the fact that our findings show a higher prevalence than at other universities in Turkey, we hold that the thought, planning, or attempt of suicide are different terms, and our inclusion of the two different terms of suicide planning and suicide attempt in the same question may have affected the results.…”
Section: The Prevalence Of Risky Behaviorcontrasting
confidence: 58%
“…In 2010, suicide was the third leading cause of death among college-aged young adults, accounting for 14.1% of deaths in this age group (CDC, 2013). Furthermore, 24% of college students reported suicide ideation (Westefeld et al, 2005), a much higher percentage than the general population (3.3% experienced suicide ideation; Kessler, Berglund, Borges, Nock, & Wang, 2005). Taken together, these data indicate an imperative need to examine risk factors for suicide among college-aged individuals.…”
Section: Introductionmentioning
confidence: 92%